2022
DOI: 10.1158/2326-6066.cir-21-0870
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Landscape of Human Melanoma Brain Metastases in Response to Immune Checkpoint Inhibition

Abstract: Melanoma-derived brain metastases (MBM) represent an unmet clinical need because central nervous system (CNS) progression is frequently an end-stage of the disease. Immune checkpoint inhibitors (ICI) provide a clinical opportunity against MBM; however, the MBM tumor microenvironment (TME) has not been fully elucidated in the context of ICI. To dissect unique elements of the MBM TME and correlates of MBM response to ICI, we collected 32 fresh MBM and performed single-cell RNA sequencing of the MBM TME and T-cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…(A) UMAP dimensionality reduction of cells, annotated as all cells clustering (right panel) and FasL expression level in a specific cell population (left panel). Datasets were extracted from the Single Cell PORTAL (Broad Institute) . (B) UMAP dimensionality reduction of cells, annotated as T cell subpopulations (right panel) and FasL expression level in specific T cell subpopulations (left panel).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(A) UMAP dimensionality reduction of cells, annotated as all cells clustering (right panel) and FasL expression level in a specific cell population (left panel). Datasets were extracted from the Single Cell PORTAL (Broad Institute) . (B) UMAP dimensionality reduction of cells, annotated as T cell subpopulations (right panel) and FasL expression level in specific T cell subpopulations (left panel).…”
Section: Resultsmentioning
confidence: 99%
“…Human Patient Tumor Sample Single-Cell RNA Sequencing (scRNA-Seq) Datasets. Human melanoma patient scRNA-Seq datasets were collected from the Single Cell PORTAL (Broad Institute) 76 and GEO database (GSE115978). 77 Human normal tissue single-cell datasets were collected from the data deposited in the Single Cell PORTAL.…”
Section: Methodsmentioning
confidence: 99%
“…EMT is a complex biological process, and the regulatory network consists of multiple miRNAs and target genes, and its role in predicting GC patients has received increasing attention [15]. Many studies have reported that the EMT process is related to the lymph node metastasis process of malignant tumors [16].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a complex biological process, and the regulatory network consists of multiple miRNAs and target genes, and its role in predicting GC patients has received increasing attention [15]. Many studies have reported that the EMT process is related to the lymph node metastasis process of malignant tumors [16].…”
Section: Discussionmentioning
confidence: 99%